Induced Packaging of Cellular MicroRNAs into HIV-1 Virions Can Inhibit Infectivity - Hal P. Bogerd (American Society for Microbiology, 2017)
ABSTRACT Analysis of the incorporation of cellular microRNAs (miRNAs) into highly purified HIV-1 virions revealed that this largely, but not entirely, mirrored the level of miRNA expression in the producer CD4+ T cells. Specifically, of the 58 cellular miRNAs detected at significant levels in the producer cells, only 5 were found in virions at a level 2- to 4-fold higher than that predicted on the basis of random cytoplasmic sampling. Of note, these included two miRNAs, miR-155 and miR-92a, that were reported previously to at least weakly bind HIV-1 transcripts. To test whether miRNA binding to the HIV-1 genome can induce virion incorporation, artificial miRNA target sites were introduced into the viral genome and a 10- to 40-fold increase in the packaging of the cognate miRNAs into virions was then observed, leading to the recruitment of up to 1.6 miRNA copies per virion. Importantly, this high level of incorporation significantly inhibited HIV-1 virion infectivity. These results suggest that target sites for cellular miRNAs can inhibit RNA virus replication at two distinct steps, i.e., during infection and during viral gene expression, thus explaining why a range of different RNA viruses appear to have evolved to avoid cellular miRNA binding to their genome. IMPORTANCE The genomes of RNA viruses have the potential to interact with cellular miRNAs, which could lead to their incorporation into virions, with unknown effects on virion function. Here, it is demonstrated that wild-type HIV-1 virions essentially randomly incorporate low levels of the miRNAs expressed by infected cells. However, the specific incorporation of high levels of individual cellular miRNAs can be induced by insertion of cognate target sites into the viral genome. Of note, this results in a modest but significant inhibition of virion infectivity. These data imply that cellular miRNAs have the potential to inhibit viral replication by interfering with not only viral mRNA function but also virion infectivity.